Three new species of the leafhopper genus Processina (Hemiptera: Cicadellidae: Mileewinae) from Thailand - He, Hongli; Yang, Maofa; Yu, Xiaofei (Zootaxa, 2018)
Three new species of the leafhopper genus Processina Yang, Deitz & Li, 2005 are described from Thailand: Processina chandrai sp. nov., P. topoarmata sp. nov. and P. kamphaengensis sp. nov. A checklist to the species of the genus and a key for their separation are provided.